The role of endowments in advancing education and socio-economic outcomes: a systematic literature review - Md Kamdari, Nor’ Azurah; Abd Jalil, Mohamad I’sa; Abd Karim, Mohd Rahimie (UiTM Cawangan Johor, 2025)
Waqf and endowments have been regarded as key strategies of financing education and socio-economic growth. Despite their importance, their functions in the modern education and economic systems have not been completely comprehended. This systematic literature review (SLR) aims to investigate the role of endowments and waqf in enhancing education and socio-economic outcomes. Scopus and Web of Science databases were searched using the advanced search function, and the strict screening process was applied to pinpoint relevant studies. In total, 19 main articles have been chosen to be discussed in depth. In addition, the research conformed to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The assessed topics include endowment and philanthropy management in education, waqf and the building of the Islamic school, cognitive development, and socio-economic impacts. Quantitative substantiations demonstrate the importance of sound fund management, and some studies have focused on the importance of professional expertise in maximizing endowment use to guarantee sustainability in the long term. The findings indicate the prospects of endowments and waqf in satisfying educational deficiencies, supporting financial viability, and advancing equality of development. Nevertheless, issues still exist, including donor influence, misappropriation of finances, and regional inequities that have to be phased out and co-managed with flexible solutions. In a nutshell, the review is useful to policymakers, educational institutions, and stakeholders and may be adopted as a launching point to leverage endowments and waqf as a tool to resolve global education and development challenges.